Menumbuhkan Spirit Toleransi Generasi Mileneal Dalam Mereduksi Isu Primordial Pada Pemilu Tahun 2024 Di Kabupaten Semarang - Setiajid Setiajid; Martien Herna Susanti; Slamet Sumarto; Rahel Gloria Pranoto (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
In the 2024 elections, the use of social media is often used by a number of elites to spread the issue of primordialism based on ethnic, religious, and regional sentiments as a strategy to gain support. Partner problems: (1) the millennial generation's low knowledge about elections; and (2) the high potential for utilization of the millennial generation by participants in the 2024 General Election. The objectives of the service activities are: (1) to provide knowledge about the importance of the intelligent millennial generation in using their right to vote in the 2024 General Election, and (2) to provide awareness of the importance of the spirit of tolerance in reducing primordial issues in the 2024 elections. The method for implementing community education is in the form of socialization. The results of the activity showed that, after participating in the socialization, participants were able to understand the urgency of voting rights and detect hoax news and black campaign information that misled voters. The spirit of tolerance needs to continue to be developed in order to minimize primordial issues that have the potential to cause national disintegration. In conclusion, tolerance is important to ward off issues of primordialism which have a disintegrating impact.